2013
DOI: 10.1155/2013/461815
|View full text |Cite
|
Sign up to set email alerts
|

Primary Intimal (Spindle Cell) Sarcoma of the Heart: A Case Report and Review of the Literature

Abstract: Intimal (spindle cell) sarcomas of the left atrium are extremely rare primary cardiac tumours with three cases reported (Li et al. (2013), Cho et al. (2006), and Modi et al. (2009)). We present a 69-year-old man who first came to medical attention after experiencing abdominal discomfort. He had a 30 lb weight loss apparently due to dieting. He denied any other constitutional symptoms. His symptoms persisted despite a course of antibiotics for presumed diverticulitis. Laboratory values were within normal limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
100
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(101 citation statements)
references
References 20 publications
1
100
0
Order By: Relevance
“…These tumours more commonly present in the large blood vessels. Their course is highly aggressive, with a median survival of 3 months to 1 year 1. Our case describes the sixth such documented case of left atrial intimal sarcoma and, to the best of our knowledge, is the first such case presenting with neurological signs and symptoms.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…These tumours more commonly present in the large blood vessels. Their course is highly aggressive, with a median survival of 3 months to 1 year 1. Our case describes the sixth such documented case of left atrial intimal sarcoma and, to the best of our knowledge, is the first such case presenting with neurological signs and symptoms.…”
Section: Introductionmentioning
confidence: 73%
“…While the median survival is at 3 months, one group described the case of a 48-year-old man who survived 11 years after initial diagnosis 8. Ibrahim et al 1 reported a case of a 69-year-old man presenting with abdominal discomfort in the setting of recent significant weight loss. Recently, a Canadian group described a case of left atrial intimal sarcoma presenting with signs of congestive heart failure 6.…”
Section: Discussionmentioning
confidence: 99%
“…The locoregional recurrence or the appearance of metastasis happens during the first year [7]. Patients with malignant heart tumors of the left side have more frequent distant metastases, while the malignant heart tumors of the right side have more locally advanced disease [7].…”
Section: Discussionmentioning
confidence: 99%
“…These cellular features, and the presence of necrosis, define its histologic grade, which has prognostic implications [1,5,9]. Only one case reported osteoid and bone formation in a "spindle cell sarcoma of the heart" [2] and another two cases reported with chondroid differentiation [10,11], but there are no previous intermediate-grade cases with osseous metaplasia in MFS. Immunohistochemistry profiling shows an intense reactivity for vimentin in all documented cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac sarcomas are unusual and constitute 10% of cardiac tumors [1], angiosarcoma being the most common and representing 37% of cardiac sarcomas [2]. However, primary myxofibrosarcoma (MFS) is a very rare entity, with no more than 22 cases reported since 1963, which was presented as an occlusion of the bifurcation of aorta [3].…”
Section: Introductionmentioning
confidence: 99%